Envelope method for the germination test of Mombasa grass - Jeromini, Tatiane Sanches [UNESP]; Botassini, Murilo Petrassi; Barros, Renato Teo de [UNESP]; Martins, Cibele Chalita [UNESP] (Univ Estadual Londrina, 2021)
The Rules for Seed Analysis reports the use of a paper envelope to allow use of the germination test with small seeds but does not provide any method or use recommendation. As Mombasa grass has high quality and commercial importance, the objective of this study was to evaluate the viability of the envelope method in the germination test of Mombasa grass seeds, with the aim of achieving greater result accuracy and improvement of seed quality analysis processes in laboratories. The germination of eight lots of Mombasa grass seeds was evaluated with two sowing methods (on paper and in paper envelope). The moisture content and the first germination count were also determined. The experiment was conducted with a completely randomized design. The data were analyzed in a 2 x 8 factor scheme (sowing methods x lots), with four repetitions. The data were subjected to analysis of variance using the F test and when significant, treatment means were compared using the Tukey's test at 5% probability. Results showed that the envelope method is efficient for the germination test of Mombasa grass seeds and can be easily used by seed analysis laboratories, as it present results equivalent or superior to those obtained using the traditional method on paper, while occupying only 2/5 of the germination chamber space used in the conventional method.
Keywords: Economics; Efficiency; Seed laboratory; Panicum maximum